Unusual case of iron overload with cancer-mimicking abdominal splenosis. (16th May 2018) - Marchi, Giacomo; Avesani, Giacomo; Zamò, Alberto; Girelli, Domenico
Abstract : A 48-year-old man, former alcohol abuser and drug addicted, was referred to our tertiary referral centre for iron disorders because of marked hyperferritinaemia. His clinical history revealed chronic hepatitis C, ß-thalassaemia trait and post-traumatic splenectomy at age of 22. MRI-estimated liver iron content was markedly elevated, while first-line genetic test for haemochromatosis was negative. Alpha-fetoprotein was increased but liver ultrasonography did not reveal focal liver lesions. Multiphasic contrast-enhanced CT confirmed this result but showed two abdominal masses (diameter of 9 cm and 7 cm, respectively) among bowel loops, strongly suspicious for cancer. However, biopsy of one of the masses led to the final diagnosis of abdominal splenosis.